Podatek od towarów i usług w świetle innych podatków państwowych w Polsce w latach 2000-2004 - Olkowska, Wiesława (The Tax on Goods and Services (VAT) against Other State Taxes in Poland between 2000 and 2004, 2007)
The paper covers two lines of research. The first one led to establishing the actual status of receipts and arrears in the tax on goods and services as compared to other state taxes in Poland between 2000 and 2004. The receipts from the tax on goods and services had the largest, over 40% share in the global amount of revenue from state taxes. As a consequence they played the leading role in development of state budget revenues. The trends in increase and decrease of the tax on goods and services arrears were presented together with the reasons for those changes. Establishment of large amounts of VAT arrears in restructuring processes is also highlighted. The second line of research focuses on the level of VAT taxpayers indebtedness levels. The determined values of indices between 2000 and 2004 showed the highest arrears of taxpayers in VAT payments as compared to other state taxes and a slight increasing trend between 2003 and 2004. The studies were also expanded by presenting the levels of VAT arrears by province
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 285-293